(untitled) (Nordic Journal of Practical Theology, 2020)
he aim of the following article is to analyze how employees in Asarums pastorate perceive that different aspects of inclusion in the Church of Sweden worship services are challenged, shaped and changed as a consequence of a two year project with the purpose of increasing people’s inclusion. The theoretical understanding of inclusion is theoretically understood as a consequence of different and cooperative aspects. The jointly defined activity is at the center of inclusion in the church service. The context and questions of power are a kind of condition. Of importance for people’s participation are also formal as well as informal inclusion, interaction, safety, autonomy, commitment, and identification.The result shows that the employees describe how several aspects have deepened during the project while others are perceived to be difficult to influence at all. Changes are primarily described among the employees themselves and not in the larger congregational context. Inclusion among the employees in the church service was far from obvious when the project started and came to require their time as well as commitment to an extent that could not be foreseen